Lower to Middle Ordovician evolution of peri-Laurentian arc and backarc complexes in Iapetus: Constraints from the Annieopsquotch accretionary tract, central Newfoundland - Zagorevski, A.; Rogers, N.; van Staal, C. R.; McNicoll, V.; Lissenberg, Cornelis Johan; Valverde-Vaquero, P. (Geological Society of America Bulletin, 2006)
The Annieopsquotch accretionary tract in Newfoundland is composed of a series of west-dipping structural panels, each containing remnants of ophiolitic and arc-backarc complexes of Laurentian affinity formed during the Ordovician closure of Iapetus. Panels were transferred from an upper-plate to a lower-plate setting during their Middle to Late Ordovician accretion to the Laurentian margin and become progressively younger eastward. Geochronological data indicate a complex and rapid history of generation and accretion of peri-Laurentian suprasubduction zone rocks. The rapid changes in tectonic environments and the complexity of the relationships are analogous to the complex arc-backarc relationships observed in the western Pacific today. The recognition of the peri-Laurentian provenance of these units based on stratigraphy, geochronology, isotopes, and geochemistry defines the position of the Red Indian Line, the fundamental suture zone in the northern Appalachians, but more importantly enables the development of a realistic tectonic model for the Annieopsquotch accretionary tract involving both thrust and sinistral transcurrent displacements. The oldest and most inboard unit in the Annieopsquotch accretionary tract is the Annieopsquotch ophiolite belt (ca. 480 Ma), which marks the initiation of subduction outboard of the Laurentian margin. The Lloyds River ophiolite complex (ca. 473 Ma) preserves a fragment of younger, more mid-ocean-ridge–like backarc-oceanic crust than the adjacent, structurally overlying Annieopsquotch ophiolite belt. The Lloyds River ophiolite complex originated as a backarc to the Buchans Group (ca. 473 Ma) ensialic bimodal calc-alkaline arc. The panels containing the Annieopsquotch ophiolite belt and Lloyds River ophiolite complex were stitched and overlain by ensialic arc rocks of the Otter Pond Complex (ca. 468 Ma) immediately after their accretion to composite Laurentia together with the structurally underlying Buchans Group. The youngest, structurally lowest two panels comprise the ...